Energy balance, water use efficiency, and photochemistry of two globally cultivated rainfed cactus species - Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Morais, José Edson Florentino de; Tang, Xuguang; Souza, Luciana Sandra Bastos de; Souza, Carlos André Alves de; Santos, Wilma Roberta dos; Marin, Fabio Ricardo; Araújo Júnior, George do Nascimento; Alves, Cléber Pereira; Silva, Gabriel Italo Novaes da; Leite, Renan Matheus Cordeiro; Salvador, Kaique Renan da Silva; et al. (Elsevier, 2025)
Linking knowledge of energy fluxes and evapotranspiration (ET) in cacti is useful for understanding plant growth, which acts as an extremely important feed source for dairy farming. However, there is little quantitative understanding of the latent (LE) and sensible (H) heat fluxes in drylands of cactus. We therefore investigated the feedback from plants of Nopalea and Opuntia on an interannual and seasonal scale, of the surface energy balance (SEB) components, morphophysiological parameters, biomass, water relations and photochemical relationships during the wet and dry seasons of 2018–2021 in the semi-arid region of Brazil. To analyse the data, four periods were selected (dry season, wet season, and dry-wet and wet-dry transitions). Our results showed that the LE (105.26 W m−2) of Opuntia was 77 % greater than that of Nopalea. In all seasons, H was the SEB component with the highest energy consumption in the two cacti, with LE the second most affected. Under Nopalea, the soil heat flux increased at the surface (112 %) during the wet and dry seasons (a mean of 1.61 MJ m−2 day−1). The mean ET of Nopalea and Opuntia was 1.71 and 1.96 mm day−1 respectively. The H/Rn ratio showed decreasing behaviour from the dry to the wet season, with a reduction of 37 % in Nopalea and 14 % in Opuntia. The NDVI ranged from 0.19 to 0.67 (Nopalea), and 0.17–0.70 for Opuntia, similar to the Chlorophyll Index, which maintained the seasonality of the NDVI. Overall, we found spatial patterns for the Photochemical Reflectance Index of −0.01 to 0.14 for Nopalea and Opuntia. Under the same conditions, Opuntia showed a higher growth rate and net assimilation rate. The mean cladode water content was 86 % in Nopalea and 89 % in Opuntia. Biomass and water use efficiency were greater in Opuntia (56.01 Mg ha−1 and 7.54 kg m−3 respectively). We also found that these comparisons indicate greater sensitivity in Nopalea, and more-significant quantification of the SEB in Opuntia.
Keywords: CAM plants; Energy partitioning; Latent heat flux; Semi-arid